The role of basic psychological need satisfaction as a mediator between friendship quality and life satisfaction - Putri, Fanny Eka; Muttaqin, Darmawan (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2022)
Friendship quality plays an essential role for adolescents in achieving optimal life satisfaction. However, previous studies have failed to explain friendship quality and life satisfaction fully. This study examines the role of basic psychological need satisfaction in the relationship between friendship quality and life satisfaction. A total of 450 respondents consisting of three groups of 150 early, middle, and late adolescents participated in this study. Data were collected using quota and convenience sampling methods. Friendship quality, basic psychological need satisfaction, and life satisfaction were measured using the McGill Friendship Questionnaire–Friend's Functions, Sub-scale Satisfaction of the Basic Psychological Need Satisfaction and Frustration Scale, and the Indonesian version of the Satisfaction with Life Scale. The hypothesis was tested using regression analysis and SOBEL macro for SPSS. The results show that basic psychological need satisfaction acts as a full mediator between friendship quality and life satisfaction (indirect effect = .330, z = 8.383, p < .05). In addition, the satisfaction of the need for autonomy, competence, and relatedness can also be a full mediator between friendship quality and life satisfaction. This finding can be an alternative in explaining this relationship between friendship quality and life satisfaction. In addition, the findings can also be used to develop mental health programs for adolescents.